Staged Single-Ventricle Palliation in an Infant with Hemoglobin SC Disease - Law, Mark A. (Texas Heart Institute, 2007)
Staged single-ventricle palliation is used to treat many cyanotic congenital heart diseases. Hemoglobin sickle cell disease is associated with anemia and significant vascular sickling sequelae, which increase the risk associated with single-ventricle palliation. To our knowledge, there are no reports in the English-language medical literature of single-ventricle palliation having been performed on a patient who had either sickle cell anemia or sickle cell–hemoglobin C disease. Herein, we discuss our clinical and surgical management of an infant with tricuspid atresia type IA and hemoglobin sickle cell disease who survived single-ventricle palliative procedures through the 2nd stage of a bidirectional Glenn anastomosis.